Identifikasi Potensi Ruang dalam Pabrik Gula Pangka dengan Pendekatan Adaptive Reuse - Aulia Safira; R. Siti Rukayah (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Identification of Space Utilization in Pangka Sugar Factory with Adaptive Reuse ApproachAdaptive reuse is a strategy in historic building preservation that aims to maintain key architectural elements while introducing new, relevant functions (Plevoets & Van Cleempoel, 2019). Pangka Sugar Factory, as a colonial industrial building, has the potential for redevelopment through Adaptive reuse, but its space utilization has not been systematically analyzed. This research aims to identify the existing conditions and spatial utilization of Pangka Sugar Factory to formulate an appropriate Adaptive reuse strategy. The study employs a qualitative approach using field observations, documentation studies, and spatial mapping analysis to assess structural integrity and functional adaptability (Bullen & Love, 2011). The findings indicate that many spaces within the factory remain underutilized and face structural degradation. The proposed recommendations focus on preserving key historical elements while repurposing specific areas for contemporary functions such as cultural, commercial, and educational uses, ensuring long-term sustainability.